Jurisprudence of the European court of human rights in the choice of precautionary measures in criminal proceedings: legal realities and perspectives - Romantsova, Svitlana; Zinkovskyy, Igor; Komisarchuk, Ruslan; Balatska, Olha; Strelbitska, Lesia (Cuestiones Políticas, 2020)
The article deals with the problems of application of the decisions of the European Court of Human Rights (ECHR) in the selection of precautionary measures in criminal cases in accordance with Ukrainian law. Since the procedural legislation of Ukraine is currently not perfect in the framework of the establishment and regulation of the application of precautionary measures, the decisions of the ECHR serve as an indispensable regulator of this issue. The objective of the work is to study the peculiarities of the application of the jurisprudence of the European Court of Human Rights in the selection of precautionary measures in criminal proceedings. The subject of the investigation is the jurisprudence of the ECHR in the context of the choice of precautionary measures in the criminal process. The research methodology included and combined the dialectical method, logical and legal method, analysis, synthesis. By way of conclusion, the study shows that the practice of the ECHR is mandatory to take into account not only the courts but also the investigators and prosecutors, who legally have the right to request the court to apply such precautionary measures.